Advances and new frontiers for immunotherapy in colorectal cancer: Setting the stage for neoadjuvant success? - Sumransub, Nuttavut (Mol Ther Oncolytics, 2021)
Immunotherapy in the metastatic setting has drastically altered the landscape of treatment for various types of malignancy, including colorectal cancer. The category of immune checkpoint inhibitors has especially emerged as a class of therapy predicated on a more comprehensive understanding of immune cell-cancer cell regulation and evolution of the tumor microenvironment over time. Strategies including adoptive cellular therapies, tumor vaccines, and antibodies have also demonstrated the ability to enhance antitumor immunity. In this article, we provide a comprehensive review of the current landscape of immunotherapeutic strategies in colorectal cancer and provide insight into how these strategies may evolve in the next decade and be adapted to more localized forms of cancers of the colon and rectum. We provide particular focus on various combination approaches under investigation for reversing cancer-induced immunosuppression, especially in mismatch repair-proficient/microsatellite-stable colorectal tumors. Finally, we summarize current understanding on a recently identified integral factor in local immune regulation, the colonic microbiome. The aim of this article is to identify current challenges and barriers to improvement and to specify opportunities for applying knowledge in the immunotherapy sphere to rational design of clinical trials intended to improve survival and related outcomes in patients treated in the neoadjuvant setting.